Prevalence and size variation of feather mite, Analges slovakiensis Dabert, Mironov & Janiga, 2018, on the host Alpine accentor, Prunella collaris (Scopoli, 1769) - M. Janiga; N. Marčanová; Z. Kompišová Ballová (The European Zoological Journal)
Analges slovakiensis Dabert, Mironov and Janiga, 2018 is a mite species that has co-evolved with the Alpine accentor Prunella collaris (Scopoli, 1786), an alpine songbird. We captured 150 Alpine accentors in the Western Carpathians in Slovakia to study the ecology and morphology of Analges slovakiensis. Seasonal variations in size were found only in females. In spring, female mites were larger with a higher intensity of infestation, however with the lowest prevalence. In contrast, autumn generations of female mites were smaller and the intensity of infestation by mites was lower due to a large dispersal to host birds. The prevalence of mites was high in autumn and in summer. Males of A. slovakiensis did not differ in size or shape among seasons. Morphophysiological plasticity combined with population dynamics allows the mites to survive effectively on hosts living at high altitudes in the mountains. The results also suggest that A. slovakiensis spreads through vertical transmission, as it radiates and increases in size during breeding season.